El bloqueo invisible y la caída de Allende - Sigmund, Paul E. (Estudios Internacionales, 1974)
One salient aspect of the military coup that toppled Salvador Allende as Chilean president in September 1973 has been the assumption that the ultimate responsibility for the tragic destruction of Chilean democracy rested with the United States. In some circles, the charge includes an accusation of secret US involvement in the coup. It is based on what President Allende himself called, speaking before the United Nations in December 1972, "the invisible financial and economic blockade" exercised by the United States against his government. This leads us to ask ourselves: Was there really an undeclared economic war between the Nixon government and Salvador Allende? This argument is not convincing. A subcommittee of the Senate Foreign Relations Committee, led by Senator Gale McGee, has recently investigated this accusation and their conclusion is that there is no evidence so far of involvement from the United States.